2015
DOI: 10.1177/0363546515573935
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Edema in the Knee and Its Influence on Clinical Outcome After Matrix-Based Autologous Chondrocyte Implantation

Abstract: Midterm clinical results of the matrix-based third-generation ACI showed a substantial amount of BME over a 36-month follow-up, but this did not correlate with worse clinical outcome. Patients with femoral cartilage defects were more often affected than were those with patellar cartilage defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
2
39
2
1
Order By: Relevance
“…Symptomatic defect-associated bone marrow edema were found in 8.4 % (n=3) of the cases. In a previous study, bone marrow edema after autologous chondrocyte implantation was analysed [13]. In this study, it was shown that bone marrow oedema appears in over 78 % of the cases.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Symptomatic defect-associated bone marrow edema were found in 8.4 % (n=3) of the cases. In a previous study, bone marrow edema after autologous chondrocyte implantation was analysed [13]. In this study, it was shown that bone marrow oedema appears in over 78 % of the cases.…”
Section: Discussionmentioning
confidence: 83%
“…All defects were treated with NOVACART®3D (TETEC AG, Reutlingen, Germany). The operation technique was performed as described in a previous study [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative subchondral bone oedema does not correlate with poor outcomes after ACI 38 52. However, a systematic review of the literature indicated a correlation between subchondral bone changes and the progression of knee osteoarthritis and the need for a total knee replacement 53…”
Section: Failure Mechanismsmentioning
confidence: 99%
“…Dieser Zusammenhang ließ sich im postoperativen Verlauf nach knorpelregenerativen Maßnahmen jedoch nicht nachweisen. Hier besteht keine Korrelation zwischen dem Auftreten und der Ausprägung von postoperativen Knochenmarködemen und dem postoperativen Outcome [12].…”
Section: Symptome Und Diagnostikunclassified